2003
DOI: 10.1016/s0969-2126(03)00002-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fold Revealed by the Structure of a FAS1 Domain Pair from the Insect Cell Adhesion Molecule Fasciclin I

Abstract: Fasciclin I is an insect neural cell adhesion molecule consisting of four FAS1 domains, homologs of which are present in many bacterial, plant, and animal proteins. The crystal structure of FAS1 domains 3 and 4 of Drosophila fasciclin I reveals a novel domain fold, consisting of a seven-stranded beta wedge and a number of alpha helices. The two domains are arranged in a linear fashion and interact through a substantial polar interface. Missense mutations in the FAS1 domains of the human protein betaig-h3 cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 26 publications
7
88
0
Order By: Relevance
“…Because no crystal structures of FLA4 or FEI RLKs are available, we approached this question using molecular modelling. One of the crystal structures of Fas1 domains in the Protein Data Bank belongs to human transforming growth factor-beta-induced protein (TGFBIp) having four Fas1 domains (PDB ID 5NV6, 10 ) and another one shows the Fas1-3 and Fas1-4 domains of Drosophila fasciclin I (PDB ID 1O70, 11 ). We used SwissModel to make a homology model of FLA4 using these two crystal structures as a template.…”
Section: Resultsmentioning
confidence: 99%
“…Because no crystal structures of FLA4 or FEI RLKs are available, we approached this question using molecular modelling. One of the crystal structures of Fas1 domains in the Protein Data Bank belongs to human transforming growth factor-beta-induced protein (TGFBIp) having four Fas1 domains (PDB ID 5NV6, 10 ) and another one shows the Fas1-3 and Fas1-4 domains of Drosophila fasciclin I (PDB ID 1O70, 11 ). We used SwissModel to make a homology model of FLA4 using these two crystal structures as a template.…”
Section: Resultsmentioning
confidence: 99%
“…The L R proteins can be grouped into three classes on the basis of their structures (Extended Data Fig. 3f, g): the first class includes L R 1-L R 3 and contains the Pfam00427 domain; the second class possesses a previously unidentified, conserved chromophore-binding domain; and the third class has only one member (L R 9) and bears the FAS1 domain, which is critical for cell adhesion 29 . Figure 2 illustrates how a rod (Rb is used here) is assembled.…”
Section: Rod Linker Proteinsmentioning
confidence: 99%
“…These proteins share a similar conformation distinguished by a structural element in the middle and extensions at both sides (Extended Data Figs 3f, g, 8). The structural element comprises a long α -helix in L RC 4 and L RC 5 and a FAS1 29,33 domain in L RC 6 (Extended Data Figs 3f, g, 8). The long α -helix of L RC 4 and L RC 5 spans one α -subunit of the core trimer (Extended Data Fig.…”
Section: Rod-core Linker Proteinsmentioning
confidence: 99%
“…The protein also appears to be involved in endothelial cell-matrix interactions during vascular remodeling and angiogenesis (21) and as a negative regulator of mineralization during cartilage differentiation and osteogenesis (22)(23)(24). Mutations in the human ␤ig-h3 gene (TGFBI) have been linked to several autosomal dominant corneal dystrophies (4) characterized by severe visual impairment resulting from the progressive accumulation of ␤ig-h3-containing protein deposits in the corneal matrix (25,26).To elucidate the function of ␤ig-h3 within the extracellular matrix, studies in our laboratory have focused on the localization, molecular forms, and matrix interactions of ␤ig-h3 within various tissues. Ultrastructural localization studies on developing tissues showed that, in most instances, ␤ig-h3 was loosely associated with collagen fibers although, in developing kidney, labeling was also observed close to the tubular and capsular basement membranes.…”
mentioning
confidence: 99%